A Critical Review of the Development of the Research and Innovation Policy Practice in Yugoslavia in the Period 1945–1991 - Semenčenko, Dušica M.; Kutlača, Đuro G. (Sociološki pregled, 2019)
Our assumption and the frst hypothesis of the research is that prior development of the science and technology system in former Yugoslavia had a major impact on the current status of the national innovation systems of countries which are former Yugoslav republics. The second hypothesis, which we elaborated in this paper, is that the science system in former Yugoslavia was strongly inﬂuenced by the sociopolitical and economic framework. With these aims, we analysed and presented four characteristic periods of the Yugoslav science and technology system afer the Second World War. In conclusions we emphasized the key inherited practices and repercussions on the management of research and innovation systems in former Yugoslav countries, which can be grouped around fve main issues. Keywords: science and technology system, research and innovation policy, development, Yugoslavia